2021
DOI: 10.1002/qute.202100055
|View full text |Cite
|
Sign up to set email alerts
|

Finding Solutions of the Navier‐Stokes Equations through Quantum Computing—Recent Progress, a Generalization, and Next Steps Forward

Abstract: Efficient simulation of a quantum system's dynamics is expected to be an important application area for quantum computers as existing classical computers cannot do this. However, quantum systems are not unique in being hard to simulate. For example, classical nonlinear continuum systems and fields are governed by nonlinear partial differential equations whose solution is also hard for classical computers. Solving such equations is essential for many economically important industries/applications such as the ae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 65 publications
0
20
0
Order By: Relevance
“…What is even more surprising is that other disciplines away from quantum physics, yet heavily relying on numerical calculus (fluid mechanics, finance, etc) already applied quantum algorithms to their own cost-intensive problems. For instance, several works in fluid mechanics field used quantum subroutines to solve both the lattice Boltzmann (Mezzacapo et al, 2015;Todorova and Steijl, 2020;Budinski, 2021a) and the Navier-Stokes (Steijl and Barakos, 2018;Gaitan, 2020;Budinski, 2021b;Gaitan, 2021) equations. The hope is that structual mechanics will also explore the use of quantum algorithms to support expensive simulations, such as those involving material nonlinearities and large structural deformations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…What is even more surprising is that other disciplines away from quantum physics, yet heavily relying on numerical calculus (fluid mechanics, finance, etc) already applied quantum algorithms to their own cost-intensive problems. For instance, several works in fluid mechanics field used quantum subroutines to solve both the lattice Boltzmann (Mezzacapo et al, 2015;Todorova and Steijl, 2020;Budinski, 2021a) and the Navier-Stokes (Steijl and Barakos, 2018;Gaitan, 2020;Budinski, 2021b;Gaitan, 2021) equations. The hope is that structual mechanics will also explore the use of quantum algorithms to support expensive simulations, such as those involving material nonlinearities and large structural deformations.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, this work is aimed at the applied mechanics community and thus limits its focus to equations in structural mechanics. However, it must be pointed out that the field of quantum algorithms for PDEs spans many other branches of science, such as fluid mechanics (Mezzacapo et al, 2015;Steijl and Barakos, 2018;Todorova and Steijl, 2020;Gaitan, 2020Gaitan, , 2021Budinski, 2021a,b), finance (An et al, 2020;Chakrabarti et al, 2021;Fontanela et al, 2021), model discovery (Heim et al, 2021) and cosmology (Mocz and Szasz, 2021), which may also benefit from specialized reviews.…”
Section: Introductionmentioning
confidence: 99%
“…Second, their estimate of the border to localization was imprecise and has been improved to form bound (2). Third and lastly, they did not recognize the early time regime which is crucial for quantifying the maximum allowable noise in bound (3). These details are necessary in the context of few-qubit quantum simulation.…”
Section: Quantum Mapsmentioning
confidence: 99%
“…Because chaotic systems are typically modeled through numerical computation, they are one of the primary application areas for scientific computing. Examples from classical physics include simulations of molecular dynamics [1], fluid dynamics [2,3], plasma physics [4,5], Monte Carlo methods, and gravitational N-body problems. Examples from quantum physics include nonequilibrium condensed matter physics [6], chemistry [7], nuclear physics [8,9], and lattice gauge theory [10].…”
Section: Introduction 1motivationmentioning
confidence: 99%
“…In recent years, there has been a significant development of QC applications to physics problems, including simulations of classical systems. Various methods have been proposed to solve the wave equation 23 , Poisson's equation 24,25 , Maxwell's equations 26,27 , and first-order linear hyperbolic systems 28 , the Navier-Stokes equation 29,30 , the Boltzmann equation 31 , and to simulate advection-diffusion processes 32 . It was also shown that most of quantum algorithms can be considered as special cases of a more general algorithm called Quantum Singular Value Transform 33 .…”
Section: Introductionmentioning
confidence: 99%